A Genetic Propensity to High Factor VII Is not Associated with the Risk of Myocardial Infarction in Men - Doggen, C. J. M.; Cats, Manger V.; Bertina, R. M.; Reitsma, P. H.; Vandenbroucke, J. P.; Rosendaal, F. R. (Thrombosis and Haemostasis, 1998)
Several studies have examined the relation between factor VII and coronary artery disease by measuring factor VII levels in plasma and some found an association between high levels and disease. This suffers problems of interpretation concerning the causality of high factor VII levels, because factor VII levels may be affected by atherogenic risk factors and may become elevated as a consequence of atherosclerosis. We investigated the association between a genetic variant (353Arg→Gln), shown to be related to factor VII levels, and myocardial infarction in a large case-control study, including 560 cases and 644 controls. Individuals carrying the 353Arg-Arg genotype seemed to have a lower risk of myocardial infarction (odds ratio 0.80 [95% confidence interval 0.60-1.06]). In this study, we confirmed higher factor VII antigen and activity level in 529 men homozygous for the 353Arg allele compared with 115 men carriers of the 353Gln allele (around 20% higher).Our results indicate that a genetic propensity to high factor VII levels is not associated with the risk of myocardial infarction. Since we confirmed the association of the 353Arg-Arg genotype with higher factor VII levels, we conclude that high levels of factor VII are not a causal determinant of myocardial infarction.